Efektivitas Pengawasan Peraturan Bupati Tangerang Nomor 12 Tahun 2022 Tentang Pembatasan Waktu Operasional Mobil Barang pada Ruas Jalan di Kecamatan Kronjo Kabupaten Tangerang - Mohamad Arief Rifai; Hasuri Waseh (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the Effectiveness of Monitoring the Tangerang Regent Regulation Number 12 of 2022 concerning the Restriction of Operational Hours for Freight Vehicles on Roads in Kronjo District, Tangerang Regency. The purpose of this research is to understand how effectively the monitoring of the Regent Regulation Number 12 of 2022 is being implemented in relation to limiting the operational hours of freight vehicles in the Kronjo District, Tangerang Regency. This study employs a descriptive qualitative method. Data collection techniques include observation, direct interviews, and documentation. The validity of the data was tested using triangulation and member checks, based on the theory of Effective Supervision by Handoko, which includes the following indicators: Accurate, Timely, Objective and Comprehensive, Focused on Strategic Control Points, Economically Realistic, Organizationally Realistic, Coordinated with Workflow, Flexible, Operationally Instructive, and Accepted by Members of the Organization. The results of the study show that monitoring of Regent Regulation Number 12 of 2022 in Kronjo District has had a positive impact, as evidenced by a reduction in traffic congestion and accidents caused by trucks. However, the effectiveness of the monitoring is not yet optimal, as some vehicles still operate outside the permitted hours, partly due to the lack of infrastructure, such as monitoring posts in the Kronjo area.